Determine the amount of heat accumulated at the focal point of the solar oven (Texas Journal of Multidisciplinary Studies, 2022)
This article discusses the methods of creating and effectively using the design of a modern device "Solar oven" based on physical and technical solutions and using scientific advances. The high efficiency of solar radiation returns of the proposed structure and the parameters for calculating the thermal energy concentrated in the focus of the concentrator are discuses. The proposed device and method of obtaining thermal energy in the production of thermal energy is based on environmental friendliness, the differences and advantages of faceted concentrators from integrated concentrators, economic savings in terms of raw materials consumed